Afatinib in the Treatment of Advanced Non-Small Cell Lung Cancer with Rare EGFR (in exon 18-T179X) Mutation - a Case Report - Čoupková, Helena; Vyzula, Rostislav (Klinicka onkologie, 2018)
INTRODUCTION: Exon 18-T719X EGFR mutation in non-small cell lung cancer is rare, only 1-5% of all EGFR mutations. The efficacy of EGFR tyrosin kinase inhibitors in tumours with uncommon mutations is still unclear and the prediction of response of such tumours to therapy remains unexplored. CASE: A 71-year-old woman with no previous smoking history with disseminated lung adenocarcinoma with exon 18-T719X EGFR mutation was treated with afatinib. A partial response was achieved in 2 months, progression-free survival was 19 months. The dose of afatinib was reduced to 30mg/day after 3 months due to skin toxicity and stomatitis grade 2. Next reduction to 20mg/day was performed after 10 subsequent months due to leucopenia and neutropenia grade 2. CONCLUSION: With this patient, a partial response which lasted 19 months despite 50% reduction of the afatinib dose was achieved. Key words: afatinib - non-small cell lung cancer - epidermal growth factor-mutation receptor - treatment outcome - drug toxicity This article was supported by Boehringer Ingelheim. The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers. Submitted: 27. 9. 2018 Accepted: 1. 10. 2018.
Keywords: senioři; Treatment Outcome; Protein Kinase Inhibitors; výsledek terapie; Exons; ErbB Receptors; nádory plic; mutace; Adenocarcinoma of Lung; Antineoplastic Agents; Afatinib; Disease-Free Survival; nemalobuněčný karcinom plic; ženské pohlaví; protinádorové látky; Mutation; Humans; adenokarcinom plic; Carcinoma, Non-Small-Cell Lung; afatinib - non-small cell lung cancer - epidermal growth factor-mutation receptor - treatment outcome - drug toxicity This article was supported by Boehringer Ingelheim. The authors declare they have no potential conflicts of interest concerning drugs; erbB receptory; afatinib; or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers. Submitted: 27. 9. 2018 Accepted: 1. 10. 2018; inhibitory proteinkinas; Female; Aged; exony; Lung Neoplasms; přežití bez známek nemoci; products; lidé